The driving forces behind Malaysian corporate social reporting / Mustaffa Mohamed Zain - Mohamed Zain, Mustaffa (Faculty of Accountancy, 2004)
Corporate social disclosure has, since the early seventies, attracted the interest of various user groups. As a result, a long history of research into corporate social disclosure practice is observable in developed countries particularly the United States and Western Europe. However, very little attention has been focused on developing countries. This paper seeks to understand why corporations in Malaysia are disclosing social information in their annual report. Semi structured personal interviews were conducted on ten companies from various sectors to find out the reasons for disclosure. A group of financial analysts were also interviewed to understand the need for information by third party. The interviews revealed that most companies are disclosing social information due to top management awareness together with a desire to comply with the government's social policy and enhance corporate image. The study also highlights that while accountability seems to be the main emphasis for disclosing social information, legitimization of business cannot be ingored due to different market pressures, government policy and values from those of western countries.